Extreme, but not moderate climate scenarios, impart sublethal effects on polyps of the Irukandji jellyfish, Carukia barnesi - Boco, Sheldon Rey; Pitt, Kylie A; Melvin, Steven D (Science of The Total Environment, 2019)
Ocean acidification and warming, fueled by excess atmospheric carbon dioxide, can impose stress on marine organisms. Most studies testing the effects of climate change on marine organisms, however, use extreme climate projection scenarios, despite moderate projections scenarios being most likely to occur. Here, we examined the interactive effects of warming and acidification on reproduction, respiration, mobility and metabolic composition of polyps of the Irukandji jellyfish, Carukia barnesi, to determine the responses of a cubozoan jellyfish to moderate and extreme climate scenarios in Queensland, Australia. The experiment consisted two orthogonal factors: temperature (current 25 °C and future 28 °C) and pH (current (8.0) moderate (7.9) and extreme (7.7)). All polyps survived in the experiment but fewer polyps were produced in the pH 7.7 treatment compared to pH 7.9 and pH 8.0. Respiration rates were elevated in the lowest pH treatment throughout most of the experiment and polyps were approximately half as mobile in this treatment compared to pH 7.9 and pH 8.0, regardless of temperature. We identified metabolites occurring at significantly lower relative abundance in the lowest pH (i.e. glutamate, acetate, betaine, methylguanidine, lysine, sarcosine, glycine) and elevated temperature (i.e. proline, trigonelline, creatinine, mannose, acetate, betaine, methylguanidine, lysine, sarcosine) treatments. Glycine was the only metabolite exhibiting an interactive effect between pH and temperature. Our results suggest that C. barnesi polyps are unaffected by the most optimistic climate scenario and may tolerate even extreme climate conditions to some extent. Full Text